ANALISIS PEMANFAATAN DANA BANTUAN SOSIAL DAN HIBAH DI TINGKAT KABUPATEN/KOTA PADA PEMILIHAN KEPALA DAERAH TAHUN 2018 - Dwi Resti Pratiwi; Marihot Nasution (Pusat Kajian Anggaran, 2018)
This study examines the use of social assistance funds and grants ahead of the 2018 elections. This test is carried out by examining differences in the allocation of grants and social assistance funds in local governments led by incumbent leaders. The results show that there is a significant difference in the allocation of social assistance funds and grants in the first period of office and then nominate again in the next election. As long as the leaders served in the two leadership periods of 2008-2013 and 2013-2018, the allocation of social expenditure and grants in 2013 and 2017 had an average difference, where in 2013 the expenditure allocation was greater than in 2017. In 2017 was the last year the leader served in government. Differences also appear in the leadership tenure where there is still a chance for him to run for the next election. During his tenure as leader in the 2014-2018 period, the allocation of social assistance and grants in 2016 had an average allocation of social assistance funds and grants of 2.4 percent which had a statistically significant difference in 2017 (ahead of the 2018 election) where the funds were flat allocated by 3.4 percent. The allocation difference is also caused by the influence of the fiscal space of the regional government. However, from the results of linear regression, it was found that the amount of social assistance allocations and grants was not influenced by political factors such as the presence of incumbent leaders in government.